Quality, Reliability, Security and Robustness in Heterogeneous Systems : 15th EAI International Conference, QShine 2019, Shenzhen, China, November 22–23, 2019, Proceedings /: 15th EAI International Conference, QShine 2019, Shenzhen, China, November 22–23, 2019, Proceedings. (2020) - Unknown
No abstract available